DESAIN DAN IMPLEMENTASI AUTOMATIC TRANSFER SWITCH 3 SUMBER LISTRIK DILENGKAPI DENGAN AUTOMATIC MAIN FAILURE BERBASIS PLC UNTUK SISTEM 1 FASA - Usman, Usman; Hamdani, Hamdani; Habib, Andi Ikhsan; Asis, Nabila Sri Rejeki (Jurnal Teknologi Terapan, 2024)
To ensure the continuity of electrical energy distribution when using an Off-Grid PV system, overcoming the challenges posed by its intermittent nature is necessary. This requires the use of more than one source of electrical energy. This involves the use of more than one source of electrical energy. A device known as ATS and AMF facilitates switching between energy sources. This research aims to design an ATS equipped with AMF to transfer three electricity sources: Photovoltaic system, PLN, and Genset for a single-phase system, with the main control device being PLC. The test results found that the transfer time from the PV system to PLN is 39ms, while the transfer time from the PV system to the Genset or from PLN to the Genset is 5s. This transfer time includes the process of starting and warming up the generator. In this system, if the Genset is displaced to PLN or PLTS, the transfer time is 39ms. The starting of the generator set is limited to three attempts. If the generator set fails to start or is not voltage detected, the system will consider it a starting failure, indicated by the active Buzzer.